AN OVERVIEW OF LAN/WLAN IN CAD/CAM/CAE APPLICATIONS - Aditya Reza Haswendra (Universitas Sriwijaya, 2020)
Computer network is an interface of two or more computers that is built for the purpose of sharing, information, data, and resources. Computer network has nodes that serve as the origin, route, and receiver of data. Computer network is built using a combination of hardware and software. LANs and WLANs are the most common form of computer network and theya re used intensively and extensively in CAD/CAM/CAE applications. This review talks about the latest implementation of LANs/WLANs in CAD/CAM/CAE applications, their limitations, and consideration for their usage.